Kepemimpinan dalam Perspektif Islam - Abdul Aziz (ILMU USHULUDDIN, 2016)
This writing is a mapping of philosophical notions by Sunnī ‘ulamā’ (scholars) on leadership (imāmah, imamate) within Islam. The argumentation of imamate embraces seven topics: 1) the necessity of imamate, 2) imamate election, 3) imām’s qualification, 4) religious authority vs. temporal, 5) the true imamate vs. monarchy, 6) single or plural imām, 7) imām’s tasks. The article also questions a referred model of ancient imamate, the so called caliphate-state, which quarrels with the temporary system, nation-state.